Solve each system by using the Elimination Method.

1) 3x - y = 7
-2x + y = 2

1 answer

To solve the system of equations using the elimination method, we will eliminate one of the variables by adding or subtracting the equations.

The system of equations is:

  1. \(3x - y = 7\) (Equation 1)
  2. \(-2x + y = 2\) (Equation 2)

We can add the two equations together to eliminate \(y\):

\[ (3x - y) + (-2x + y) = 7 + 2 \]

Now, simplify the left-hand side:

\[ 3x - 2x - y + y = 9 \]

This simplifies to:

\[ x = 9 \]

Now that we have \(x\), we can substitute it back into either equation to find \(y\). We'll use Equation 1:

\[ 3(9) - y = 7 \] \[ 27 - y = 7 \] \[ -y = 7 - 27 \] \[ -y = -20 \] \[ y = 20 \]

Thus, the solution to the system of equations is:

\[ x = 9, \quad y = 20 \]

So, the solution is \((9, 20)\).